A new topological approach for the mean field modeling of dynamic recrystallization. (15th May 2018) - Maire, Ludovic; Fausty, Julien; Bernacki, Marc; Bozzolo, Nathalie; De Micheli, Pascal; Moussa, Charbel
Abstract: This paper proposes a new approach for mean field modeling of dynamic recrystallization. The main advantage of the presented model compared to the state of the art is based on a more precise description of the immediate vicinity and of the shape of each grain to describe microstructural evolution all along the hot deformation process. Results provided by the new model are compared to those of a former mean field formulation and those of a full field model with an explicit description of the microstructure. The predictions of the new model in terms of recrystallization kinetics and grain size distributions are satisfactory and the progress when compared to former mean field models is obvious. Furthermore, the limitation of mean field models concerning the non-realistic shape of grain size distributions has been solved in this new formulation. Graphical Abstract: Highlights: A topological model for dynamic recrystallization with grain neighborhood and grain principal lengths evolution is proposed. 3D simulations of dynamic recrystallization in 304L steel submitted to high deformation are done in few seconds. Kinetics and grain size distributions are accurately predicted when compared to simulations with explicit microstructure.